Influence of provenance on physical and mechanical properties of Angelim-pedra (Hymenolobium petraeum Ducke.) wood species - Teixeira, Julia Naves; Wolenski, Anderson Renato Vobornik; Aquino, Vinicius Borges de Moura; Panzera, Tulio Hallak; Silva, Diogo Aparecido Lopes; Campos, Cristiane Inácio [UNESP]; Silva, Sérgio Augusto Mello [UNESP]; Lahr, Francisco Antonio Rocco; Christoforo, André Luis (My University, 2021)
This research aims to investigate, with the aid of the Brazilian standard NBR 7190, analysis of variance (ANOVA—5% significance) and the regrouping bootstrap technique, the influence of the provenance regions Bonfim, Mucajaí and Claudia on the physical and mechanical properties (twenty properties and 720 determinations) of Angelim-pedra (Hymenolobium petraeum Ducke.) and to assess the possibility of estimating, via regression models (152 in all), the physical and mechanical properties investigated as a function of apparent density (ρ12) and compressive strength parallel to the grain (fc0). The results indicated equivalence in most of the physical and mechanical properties, evidencing the small influence of the tree harvest regions. From the regression models, some were considered significant by ANOVA (at the 5% level of significance), which implies that variations in ρ12 and fc0 explain variations in the values of the other estimated properties; however, the low precision indicates that it is not feasible to estimate the variables just based on the ρ12 or fc0.